2022
DOI: 10.1007/s12015-022-10463-4
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the Proteins Secreted by Equine Muscle-Derived Mesenchymal Stem Cells Exposed to Cartilage Explants in Osteoarthritis Model

Abstract: Background Osteoarthritis (OA) is a highly prevalent joint degenerative disease for which therapeutic treatments are limited or invasive. Cell therapy based on mesenchymal stem/stromal cells (MSCs) is therefore seen as a promising approach for this disease, in both human and horses. As the regenerative potential of MSCs is mainly conferred by paracrine function, the goal of this study was to characterize the secreted proteins of muscle-derived MSCs (mdMSCs) in an in vitro model of OA to evaluate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 87 publications
3
1
0
Order By: Relevance
“…Our results showed a synergistic effect of decorin and ADSCs in inflammatory joint disorder; therefore, we assumed that decorin in the matrix could modulate ADSCs immunol phenotype to enhance the anti-inflammatory effect via cytokines paracrine action on chondrocytes. In line with these data, a co-culture-secreted protein study of MSCs and cartilage explants showed a protective effect of MSCs on IL-1β induced cartilage catabolic injury by increasing the decorin secretion 24 .…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…Our results showed a synergistic effect of decorin and ADSCs in inflammatory joint disorder; therefore, we assumed that decorin in the matrix could modulate ADSCs immunol phenotype to enhance the anti-inflammatory effect via cytokines paracrine action on chondrocytes. In line with these data, a co-culture-secreted protein study of MSCs and cartilage explants showed a protective effect of MSCs on IL-1β induced cartilage catabolic injury by increasing the decorin secretion 24 .…”
Section: Discussionsupporting
confidence: 68%
“…Of note, alleviation of antigen-induced arthritis by corticosteroid administration elevated decorin mRNA levels in connective tissues 23 . Furthermore, co-culture MSCs could reduce the pro-inflammatory effect of TNFα and IL-1β on cartilage by increasing decorin secretion 24 , in line with the fact that decorin may interact with extracellular tyrosine kinase receptors for immunol signaling transduction in inflammatory diseases 25 . Given the fact that decorin-overexpressed MSCs significantly attenuate inflammation by regulating immune responses 26 , we therefore wonder whether pericellular decorin would enhance the anti-inflammatory property of ADSCs that facilitate cartilage repair.…”
Section: Introductionmentioning
confidence: 76%
“…5), as compared to explants cultured without MenSCs, suggesting a protective effect of MenSCs on cartilage ECM. Similar results were demonstrated with equine derived muscle MSCs cultivated in co-cultures with OA cartilage explants, where signi cantly lower amounts of GAGs was present in the medium of co-cultures, as compared to cartilage explants cultured alone (42). Secretion of growth factors revealed signi cantly higher levels of activin A in co-culture medium with and without IL-1β and signi cantly decreased levels of IGF-1 in co-cultures (Fig.…”
Section: Discussionsupporting
confidence: 82%
“…GAG analysis also showed a significant decrease of GAG release into the medium after co-culturing explants with MenSCs for 3, 7, and 21 days (Figure 5) as compared to explants cultured without MenSCs, suggesting a protective effect of MenSCs on cartilage ECM. Similar results were demonstrated with equine derived muscle MSCs cultivated in co-cultures with OA cartilage explants, where significantly lower amounts of GAGs were present in the medium of cocultures compared to cartilage explants cultured alone [52]. The secretion of growth factors revealed significantly higher levels of activin A in co-culture medium with and without IL-1β and significantly decreased levels of IGF-1 in co-cultures (Figure 6).…”
Section: Discussionsupporting
confidence: 81%